Optimized transesterification of unrefined palm and waste cooking oil blend to biodiesel using cement kiln dust catalyst - Mahmoud S. Hefney; Mai O. Abdelmigeed; Tamer S. Ahmed; Ibrahim M. Ismail (Scientific Reports)
Abstract Biodiesel is a sustainable alternative to fossil fuels. However, biodiesel’s economic feasibility for mass-production remains a challenge. This study investigates the use of cement kiln dust (CKD) waste as a heterogeneous catalyst for the transesterification of a mixed oil made from unrefined palm oil and waste cooking oil (WCO) to increase the cost-effectiveness. To enhance the activity of the CKD, it was treated at optimized conditions of 850 °C for 2 h. The optimal blend (60 wt% WCO) for transesterification using CKD was determined through a comparative analysis of different ratios. The WCO was first upgraded through acid-catalyzed esterification to reduce free fatty acids < 1%. The effects of reaction time, temperature, catalyst loading, and methanol-to-oil ratio on biodiesel using CKD were studied using a full factorial 2n design and response surface methodology. Optimized combinations of reaction parameters were presented that give near complete conversion, which is much higher compared to the literature. These combinations can work under different manufacturing or market challenges. The produced biodiesel meets ASTM standards. This work demonstrates the potential for using low-value waste as a catalyst and low-value raw materials for biodiesel production and highlights the importance of optimizing process parameters for economic viability.